A PACS alternative for transmitting DICOM images in a high latency environment - Veeramani, S.; Masood, M.; Sidhu, Amandeep (2014)
Picture Archiving and Communication System(PACS) is responsible for storing Digital Imaging and Communication in Medicine (DICOM) images fromradiology modalities into its database, images takes a lot of time to transfer to remote location through WAN due to large file size and slow transfer protocol. A PACS alternative system has been developed which performs basic functions of a generic PACS. Images directly from modalities are large in size by default transfer syntax of these images is Endian Explicit syntax. Changing this transfer syntax to lossless JPEG 2000 decreases the file size and because of lossless compression quality of image is still same as original image. These compressed images are then copied into Network Attached Storage working as PACS alternative. A series of test conducted in lab with multiple transfer protocol on Network Attached Storage (NAS) to find out which transfer protocol is faster under moderate speed and high latency network.